Answer:
[tex](6,\, 1)[/tex].
Step-by-step explanation:
Let [tex](a,\, b)[/tex] denote the center of this circle (where [tex]a [/tex] and [tex]b[/tex] are to be found.) If the radius of this circle is [tex]r[/tex], the equation of this circle would be:
[tex](x - a)^{2} + (y - b)^{2} = r^{2}[/tex].
Expand this equation using binomial theorem:
[tex]x^{2} - 2\, a\, x + a^{2} + y^{2} - 2\, b\, y + b^{2} = r^{2}[/tex].
Both this equation and the given equation [tex]x^{2} + y^{2} - 12\, x - 2\, y + 12 = 0[/tex] describe the same circle. Therefore, corresponding coefficients of the two equations should match one another:
Solve these two equation for [tex]a[/tex] and [tex]b[/tex]: [tex]a = 6[/tex] and [tex]b = 1[/tex].
Substitute [tex]a = 6[/tex] and [tex]b = 1[/tex] into [tex](a,\, b)[/tex] to find the center of this circle: [tex](6,\, 1)[/tex].